Mathematical modeling and simulation of electrochemical reactors: A critical review. (10th August 2021) - Rivera, Fernando F.; Pérez, Tzayam; Castañeda, Locksley F.; Nava, José L.
Abstract: Modeling and simulation of electrochemical reactors (ECRs) by computational fluid dynamics (CFD) techniques have been increasing during the last fifteen years. The need to improve the performance of existing electrolyzers or the development of new technologies has attracted the attention of the scientific community. Commercial and open-source codes are very valuable tools in pursuing such goals. ECRs studied by CFD simulations are those used in the following applications: electrosynthesis of chemicals and drugs, electrowinning of metals, chlor-alkali, redox flow batteries, and fuel cells. They also included those used in water treatment, such as electrocoagulation, electrochemical advanced oxidation processes, water disinfection, heavy metal ion removal, electro-deionization, and electrodialysis. In the context of the existing technologies, some ECRs have been improved through the characterization of the reaction environment, with some adaptations made inside the electrolyzers, such as accommodation of electrodes, use of plastic meshes acting as turbulence promoters, design of 3D printed electrodes, use of novel fluid distributors at the inlet of the cells, and optimization of the operational conditions such as flow rate, current density, the concentration of reactants and temperature. Several novel ECRs that have been built using CFD approaches for multiple fundamental studies and commercial applications are examined. Finally, an in-depth analysis of mathematical modeling scientific challenges in designing and assessing ECRs is presented.